Stress properties of diamond-like amorphous carbon - Kelires, Pantelis C. (My University, 2001)
The problem of intrinsic stress in tetrahedral amorphous carbon is studied using as a probe the concept of atomic-level stresses. These are extracted from the local energetics within the empirical potential approach. The finite temperature statistics of the system are described by Monte Carlo simulations. The general finding of these simulations is that equilibrated, annealed films that relax the external constraints and pressure possess zero total intrinsic stress, but they still contain a high fraction of sp3 sites. The same holds for the hypothetical all-tetrahedral model of a-C. This finding is in contrast to the case of non-equilibrium as-grown structures, that are left intrinsically stressed by the deposition process.
Keywords: Carbon; Temperature; Amorphous carbon; Structure; Stress